Designing learning activities to develop self-directed learning competency in teaching informatics - Kieu Phuong Thuy; Nguyen Chi Trung (International Journal of Evaluation and Research in Education (IJERE), 2024)
Currently, there are not many studies on teaching informatics in the direction of developing students’ self-directed learning (SDL) competency. The results of the survey with 235 informatics teachers in 42 provinces/cities across Vietnam showed that although they are very interested in teaching SDL, teachers are still confused about teaching methods and assessments. To improve the effectiveness of informatics teaching as well as develop SDL for students, the study proposed a method of teaching informatics in the direction of designing activities to guide students to create digital products by themselves. The pedagogical experiment on assessing SDL and learning outcomes was conducted on two experimental and control groups, selected from 87 10th grade students, in the first semester of the school year 2022-2023 at Cam Giang High school in Hai Duong, Vietnam. The results of SDL and test scores of the experimental class were higher than that of the control class (with p-value <0.005– this difference is statistically significant). This proves that the method (creating of digital products) is effective, positively affecting students’ learning, helping students develop SDL competency.